An Overview of Speech Recognition Techniques and the Progress in Speech Technology for Indian Scripts - C Patel, Bharat; M Patel, Jagin; M Kayasth, Manish (International Journal of Computer Sciences and Engineering, 2015)
Speech is widely regarded as the most natural form of communication between human beings. The field of speech recognition has facilitated the development of man-machine conversations, leading to the creation of automatic speech recognition systems. These systems enable interactions between humans and machines, and their applications are diverse and extensive. This paper aims to provide an overview of speech recognition techniques, explore the various application areas of speech recognition systems, and review the progress made in speech technology, particularly for Indian scripts. Additionally, the paper focuses on feature extraction techniques and classification methods used in speech recognition systems. The primary objective of this paper is to facilitate newcomers in understanding the flow of speech recognition and guide them in their pursuit of further research in this field.